DESAIN TUNGKU ALAT PEREBUS IKAN TERI BAGI MASYARAKAT KELOMPOK NELAYAN KARANG LABUANG - Nugroho, Agung; Sawaluddin, Sawaluddin; Ridwan, Ridwan; Wahyu, Indra (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
In producing salted fish, Karang Labuang fishing communities still use traditional tools, so that the results obtained are not optimal. The boiled process takes a long time, the short life of the tool used, the heat generated is not maximal, and the quality of salted fish is also not good. Color fading of salted fish also causes the decrease of salted fish price in the market. Consequently, the sales turnover has decreased by 75%. This has an impact on the economy and welfare of the local community because the sale of salted fish is their main income. To improve the effectiveness and efficiency of Karang Labuang fishing community in producing salted fish, there is an idea to create a boiled tool for salted fish that have been modified, either from the raw material of the container and furnace construction used. To apply this technology in the community, the first step is a survey. In survey process, the team went to the targeted place in order to study the character of the local community, so when they are given the socialization and introduction of the tool, they do not pose questions. With this tool is expected that local communities can improve the productivity and quality of their salted fish productions. Thus, it will also affect the welfare of targeted society.Keywords : fishing communities, fish, boiled tool, economy of society.